Produção heteróloga do peptídeo antimicrobiano Cp- Tionina II em Physcomitrium patens - Leal, Lara Nascimento (2022)
With the emergence of microbial strains resistant to antimicrobial drugs, world health is facing a crisis against pathogens that no longer respond to conventional treatments as they did. In this context, antimicrobial peptides (PAMs) stand out and research focusing on these molecules increases every day. However, these molecules are not produced in large quantities in the organisms of origin. To obtain large amounts of peptides, we can rely on several strategies, ranging from the isolation of the molecule directly from the organism that produces it, through synthesis and expression via a heterologous system. In this work, the heterologous production of the antimicrobial peptide Cp-Thionine II was carried out in the moss Physcomitrium patens through the CRISPR/Cas9 system using three transformation vectors pActCas9, pBNRf and pLand_cpt. After transformation, 4 transformed clones were obtained which, after confirmation by sequencing, were subjected to expression analysis via qRT-PCR where clone 1.4.2 was selected for large-scale production using a bioreactor. After 45 days of cultivation in a photobioreactor, a protein extraction from the plant tissue was performed and analyzed via MALDI-TOF as well as an antimicrobial activity assay using strains ATTC 25923 for Staphylococcus aureus and ATTC 25922 for Escherichia coli. The bioassay did not show activity due to the low presence of recombinant protein in the extract at commercial levels. However, considering the general difficulty of expressing peptides in plants, we can assume that the use of the CRISPR technique was essential for the peptide to be expressed in this system.